2005
DOI: 10.1074/jbc.m506986200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Protein Phosphatase 2A Heterotrimers Modulate Growth Factor Signaling to Extracellular Signal-regulated Kinases and Akt

Abstract: At least 99% of protein phosphorylation in eukaryotic cells occurs on Ser and Thr residues. The greater than 300 protein Ser/Thr kinases in the human genome are opposed by less than 30 protein Ser/Thr phosphatases, of which protein phosphatase 1 and protein phosphatase 2A (PP2A) 2 contribute the bulk of activity in most cell types. The notion of Ser/Thr phosphatases as promiscuous and constitutively active enzymes that simply provide the substrates for regulated kinase signaling has been challenged by the disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 61 publications
4
138
1
Order By: Relevance
“…These data are consistent with previous studies of mitogenic signaling where PP2A was found to inhibit S6K1 and mTOR was found to regulate both PP2A and S6K1 (33,34). Our data extend this interplay to neurons, further indicating that mGluR acts synergistically on a pre-existing inhibition of S6K1 by PP2A.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These data are consistent with previous studies of mitogenic signaling where PP2A was found to inhibit S6K1 and mTOR was found to regulate both PP2A and S6K1 (33,34). Our data extend this interplay to neurons, further indicating that mGluR acts synergistically on a pre-existing inhibition of S6K1 by PP2A.…”
Section: Discussionsupporting
confidence: 82%
“…To further position S6K1 phosphorylation of FMRP within the known mGluR-triggered pathway (13,23,24), we sought a link between S6K1 and PP2A, the FMRP phosphatase (22), since kinase-phosphatase modules regulate synaptic activity (41,42) and PP2A inhibits S6K1 in mitogenic signaling (33,34). We found that FMRP-IPs, at 1 or 5 min following DHPG stimulation, revealed an inverse correlation between the association of PP2A and S6K1 with FMRP in agreement with the pattern of FMRP phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8b demonstrates (Qian et al, 2005b). It is interesting that Pim-1 has been shown to transform cells in concert with both c-Myc (Verbeek et al, 1991;Shirogane et al, 1999;Ellwood-Yen et al, 2003) or Akt (Amaravadi and Thompson, 2005), and that the levels of both of these proteins are regulated by PP2A (Sears, 2004;Ugi et al, 2004;Van Kanegan et al, 2005). Using a model in which hematopoietic cells are grown in an IL-3-dependent fashion, we find that knocking down a PP2A B subunit increases viability only in Pim containing, but not in Pim knockout cells.…”
Section: Regulation Ofmentioning
confidence: 87%
“…Every family accounts for a number of isoforms, in particular the B56 family involves the alpha, beta, gamma, delta and epsilon members, which share high homology. Interestingly, B56 has been implicated in the modulation of Akt phosphorylation (Van Kanegan et al, 2005;Yin et al, 2006;Rocher et al, 2007).…”
Section: Pp2a B56 Subunits Are Calpain Substratesmentioning
confidence: 99%